Tradescantia serrana (Commelinaceae), a new species from southern Brazil, and notes on T. schwirkowskiana and T. umbraculifera - Hassemer, Gustavo; Funez, Luís A.; Ferreira, João Paulo R. (Phytotaxa, 2017)
This contribution presents and describes Tradescantia serrana, a new species from the edges of Araucaria forest in the highlands of southern Santa Catarina state, southern Brazil. Illustrations, photographs and a distribution map for the new species are provided. Here, we also typify T. umbraculifera, a species morphologically related to T. serrana, and present evidence against the synonymisation of T. schwirkowskiana with T. crassula proposed by Pellegrini et al. (2017). Furthermore, we extend the distribution of T. schwirkowskiana to Paraná state.